The energy policy of Poland until 2040 and protection of the environment against low emissions – selected issues - Radecka, Ewa (Polish Yearbook of Environmental Law, 2018)
The article is an attempt at depicting the intertwining of energy policy with the fight against low emissions and answers the question of whether this document can have a real impact on air protection in Poland. The author addresses the definitions of such terms as air protection and low emissions, and briefly outlines the key and most important – from the perspective of the topic of this article – objectives of the draft energy policy of Poland until 20401 (further: EPP2040). The article concludes with a discussion of the PEP2040 objectives in the context of the fight against low emissions and an attempt at evaluation of the adopted solutions.